The Influence of Quality of Distribution and Sales Promotion to Customer Satisfaction in PT Arasindo - Yusuf Suwandi (Journal of Management and Business Environment (JMBE), 2020)
This study addressed PT Arasindo, a furniture and furniture accessories distributor. It aimed at understanding customers’ perception on quality of distribution, sales promotion, and customer satisfaction in PT Arasindo. In particular it was to find out whether the quality of distribution, sales promotions influences customer satisfaction in PT Arasindo. This study used primary data gathered using questionnaire and analyzed using multiple regression analysis. The results show there is influence of the quality of distribution on customer satisfaction.